Effects of Device Types on Online Consumer Behavior: - Takanori Suda; Hiroaki Ishii; Taku Togawa; Takashi Yamaoka (Maketingu Janaru, 2021)
The diversification of devices used by consumers has drawn attention to the influence of devices on consumer behavior. This study examines the impact of device types, such as smartphones and personal computers, on consumers’ construal levels and the congruence between the device types and construal levels on consumer behavior. For this purpose, we conducted four studies: three online experiments and one field study. Study 1 showed that consumers perceive the target closer when they view it on a smartphone (vs. a PC). In Study 2, we found that consumers’ construal level becomes lower when using a smartphone (vs. a PC). In Study 3, we confirmed that the use of smartphones (vs. PCs) positively influences the evaluation of advertisements corresponding to lower construal levels. Finally, in Study 4, we examined the applicability of the findings from Studies 1 to 3 to the field of business by analyzing actual purchase data.